Características clínicas y epidemiológicas de los pacientes pediátricos con pancreatitis aguda del nuevo Hospital Infantil de Morelia de enero de 2021 a septiembre de 2023 - Chávez García, Mariana (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
Introduction: Acute pancreatitis (AP) in pediatrics has an incidence of 1/10,000 and predominates in women, obese, and people over 5 years old. The most common etiology is anatomical. The diagnosis is established with two criteria (clinical, biochemical or radiographic), and treatment includes fluid resuscitation, analgesia, and nutrition. Objective: Describe the clinical and epidemiological characteristics of the population with AP at the Nuevo Hospital Infantil de Morelia in the period 2021-2023. Material and methods: Observational, retrospective, descriptive, and cross-sectional study, carried out after reviewing medical records of patients with AP, without other pancreatic diseases, at the Hospital Infantil de Morelia from January 2021 to September 2023. Results: Of 33 patients, 28 complied with inclusion criteria. Of them, 53.5% were female, the average age was 12.1 years and 100% were from Michoacan (10.7% from Morelia). Seventy-five percent had AP, 25% had recurrent AP and the main etiology was undetermined. The average number of fasting days was 4.6 and 53% were fed early. Regarding the nutritional diagnosis, 28.5% were overweight, 10.7% malnourished, 7.1% obese, and the rest were eutrophic. The severity of AP was mild in 53.5%, moderate in 42.8%, and severe in 3.5%. The average hospital stay was 10.8 days, 46.4% presented complications and none died. Conclusions: AP predominates in adolescents and females. Diagnostic measures should be strengthened to reduce cases of undetermined etiology, encourage the use of ultrasound, and reserve tomography for cases of diagnostic doubt or complications. Likewise, early nutrition is recommended to improve the prognosis and reduce hospital stay.

Introducción: La pancreatitis aguda (PA) en pediatría tiene una incidencia de 1/10,000 y predomina en mujeres, obesos y mayores de 5 años. La etiología más común es anatómica. El diagnóstico se establece con dos criterios (clínico, bioquímico o radiográfico) y el tratamiento incluye reanimación hídrica, analgesia y nutrición. Objetivo: Describir las características clínicas y epidemiológicas de la población con PA del Nuevo Hospital Infantil de Morelia en el periodo del 2021-2023. Material y métodos: Estudio observacional, retrospectivo, descriptivo y transversal, realizado tras la revisión de expedientes de pacientes con PA, sin otras enfermedades pancreáticas, del Nuevo Hospital Infantil de Morelia de enero 2021 a septiembre 2023. Resultados: De 33 pacientes, 28 cumplieron criterios de inclusión. El 53.5% corresponde a sexo femenino, la media de edad fue 12.1 años y el 100% fueron originarios de Michoacán (10.7% del municipio Morelia). El 75% cursó con PA, 25% con PA recurrente y la principal etiología fue indeterminada. La media de días de ayuno fue 4.6 y el 53% fue alimentado de manera temprana. En cuanto al diagnóstico nutricional, 28.5% tenían sobrepeso, 10.7% desnutrición, 7.1% obesidad y el resto eutróficos. La severidad de la PA fue leve en 53.5%, moderada en 42.8% y severa en 3.5%. La media de estancia hospitalaria fue de 10.8 días, 46.4% presentó complicaciones y ninguno falleció. Conclusiones: La PA predomina en la adolescencia y sexo femenino. Se deben fortalecer las medidas diagnósticas para disminuir los casos de etiología indeterminada, fomentar el uso de ultrasonido y reservar la tomografía para casos de duda diagnóstica o complicaciones. Así mismo, se recomienda la nutrición temprana para mejorar el pronóstico y disminuir la estancia intrahospitalaria.
Facultad de Ciencias Médicas y Biológicas. Especialidad en Pediatría
Keywords: info:eu-repo/classification/cti/3; FCMB-E-2024-0242; Pancreatitis; Pancreatitis aguda; Pancreatitis aguda recurrente; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/18768